2008
DOI: 10.1007/s00280-008-0707-9
|View full text |Cite|
|
Sign up to set email alerts
|

Does saturable formation of gemcitabine triphosphate occur in patients?

Abstract: The results showed that first-order and nonsaturable clearance described intracellular dFdCTP formation at clinically applied doses of gemcitabine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
0
15
0
3
Order By: Relevance
“…The higher concentrations of dexmedetomidine observed in obese patients after receiving TBW-based schemes are explained by two factors: the lack of influence of fat mass on dexmedetomidine volume of distribution and impairment of dexmedetomidine clearance associated with fat mass. This impairment of clearance has not been reported for other drugs examined using either FFM or NFM as a size descriptor (gemcitabine [13], busulphan [20], ethanol [21], paracetamol [22], propofol [23]). The detection of an effect of fat mass on clearance may be due to inclusion of both non-obese and obese patients in our study.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The higher concentrations of dexmedetomidine observed in obese patients after receiving TBW-based schemes are explained by two factors: the lack of influence of fat mass on dexmedetomidine volume of distribution and impairment of dexmedetomidine clearance associated with fat mass. This impairment of clearance has not been reported for other drugs examined using either FFM or NFM as a size descriptor (gemcitabine [13], busulphan [20], ethanol [21], paracetamol [22], propofol [23]). The detection of an effect of fat mass on clearance may be due to inclusion of both non-obese and obese patients in our study.…”
Section: Discussionmentioning
confidence: 72%
“…Standard weight computed from total body weight divided by W STD or NFM STD was then used in an allometric model to predict between subject differences in clearance and volume parameters [13].…”
Section: Derivation Of the Size Descriptormentioning
confidence: 99%
“…The concentrations of intracellular dFdCTP were corrected for the mean cell volume of PBMCs to convert the units of concentration from mass per million cells to mass per volume (Cheung et al , 1982). By doing so, dFdCTP was assumed to be uniformly distributed among all of the cells in each sample as done by others (Tham et al , 2008). We tested the estimation of separate residual unexplained variance (RUV) parameters for the HPLC-UV and LC-MS/MS assays used in the analysis of gemcitabine, dFdU and dFdCTP concentrations to account for the differences in their precision and sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…A mass-balance study reported that a median of 77% (range: 30–96%) of the administered dose of gemcitabine was excreted within 24 h in urine, of which a median of 5% was excreted as unchanged gemcitabine (Abbruzzese et al , 1991). The pharmacokinetics of dFdCTP has been evaluated in circulating leukaemic cells or peripheral blood mononuclear cells (PBMCs) as a surrogate for tumour (Grunewald, 1990; Tempero et al , 2003; Tham et al , 2008). …”
mentioning
confidence: 99%
See 1 more Smart Citation